The Effect of Down Hill Training on Pencak Silat Extracurricular Scratch Speed - Ridwan Sudirman (Edumaspul: Jurnal Pendidikan, 2022)
Pencak silat extracurricular activities are movement teaching, where there is a relationship between the coach/trainer and students at school. The speed of sickle kicks is a measure of students' pencak silat abilities in building character, increasing skills, dexterity and exemplary. Thus, the purpose of this study was to see the effect of downhill training on the speed of pencak silat sickle kicks. This study used a quantitative experimental method and the sample used as the unit of analysis was 20 male students who took part in pencak silat extracurricular activities. The instruments used are Pretest, Treatment and Posttest. The data analysis technique used is the t test which looks at the difference between the results of the pretest and post-test data. The results of this study indicate that the average value of students' pretest is 15.60 while the average value of students' posttest is 20.00. The result value of t count is 26.10 and the significance value is 0.00. Based on these values, it can be concluded that down hill training has an effect on the speed of sickle kicks in the pencak silat extracurricular.